Effect of Terra Exercise on Increasing Quality of Life Scores for Postmenopausal Women - Nawang Sukestiningsih; Denny Agustiningsih; Wahyudi Istiono (Faculty of Medicine, Public Health, and Nursing, 2020)
Background: The number and proportion of the Indonesian female population aged 60 years and over from year to year have experienced a significant increase. Women who have gone through menopause and enter old age are described as having many physical and psychological changes, sometimes resulting in a crisis and psychological symptoms. Eighty percent of women report discomfort that can significantly reduce their quality of life. Terra exercise is an exercise movement that is adapted to the anatomical and physiological conditions of the elderly person’s body (low impact). Terra exercise is used to train stamina both physically and mentally. Objective: This study aimed to examine the effect of Terra exercise on the quality of life of postmenopausal women in Kemanukan Village, Bagelen District, Purworejo Regency. Method: This study used a quasi-experimental pre-test-post-test design with a control group. The samples were selected by purposive sampling with the following inclusion criteria: postmenopausal women aged 60-75 years, who did not experience kidney failure, heart disease, rheumatism, blood pressure below 160/90 mmHg, did not have a mental disorder (schizophrenia) nor violent behavior, have a level of independence in the category of sufficient or more, can communicate verbally, and willing to be respondents with a signature/thumbprint of approval to follow the study. Quality of life was measured using the Older People’s Quality of Life Questionnaire (OPQOL-35). Hypothesis testing used paired t-test and Mann-Whitney tests to see the average differences between treatment groups. Result: There was a significant change in the mean pre-test-post-test scores of quality of life of the intervention group with Terra exercise. Conclusion: Terra exercise can improve the quality of life of women after menopause.